Development of a Potential Facility Risk Index for Nuclear Safety and Security Using a Terrorism Scenario with a Hypothetical Nuclear Facility - Kot, Joeun L.; Thomas, Theodore; Harris, Jason T. (Nuclear technology, 2025)
Risk assessment involves analyzing potential accident scenarios to identify hazards and assess associated risk factors. Nuclear safety and security both aim to protect against radiation exposure, but they have developed separately with distinct risk assessment methodologies. As a result, there is a need for a comprehensive risk assessment method that covers both the safety and security aspects. The Potential Facility Risk Index (PFRI) was developed in 2020 to provide a quantitative approach to evaluating the security risk of nuclear facilities, but it does not consider safety risks. This study aims to enhance the PFRI framework by incorporating probabilistic risk assessment methods to include safety risks. It assesses the risk of a hypothetical incident caused by adversaries at a hypothetical nuclear facility after a successful theft of nuclear material, followed by the construction and detonation of a radiological dispersal device. To achieve this goal, the study utilized event tree analysis and pathway analysis for loss event assessment and consequence analysis using the MELCOR accident consequence code systems for loss magnitude. New risk criteria were also established to determine the PFRI risk score. Based on the results, the study found that the PFRI score for the hypothetical facility was 1, indicating that the risk level was negligible. Future studies incorporating other scenarios, such as sabotage and transportation, will help assess the total security risk of the facility. This method can also help facilitate the integration of risk assessments for nuclear safety and security.